Economic Imbalances: New Zealand's Structural Challenge - Jean-Pierre Andre (New Zealand Government, The Treasury, 2011)
New Zealand has for a long-time lived with a large and negative international investment position, mainly in the form of private debt intermediated through the banking system. These debts create economic risks. Fortunately New Zealand's good institutional and policy arrangements provide economic resilience to avoid and respond to economic shocks. These include: relatively transparent and prudent fiscal policy; independent monetary policy; and a floating exchange rate. This resilience has also been strengthened by relatively prudent private sector lending and borrowing. However, this does not mean New Zealanders can be complacent. History shows that high levels of debt secured against elevated asset prices tend to magnify the negative impacts of economic shocks, or can cause persistent slow growth. This paper departs from typical discussions of debt imbalances by suggesting New Zealand's private debts could reflect decisions that may have been poorly made for some time. This results from long-term structural and fiscal policy settings that may have discouraged saving. In turn, this may have contributed to tighter monetary conditions than otherwise needed for price stability. This contributed to the stifling of tradables production to the detriment of economic growth. Like the recent Canterbury earthquakes, the nature of potential macroeconomic shocks and the likelihood of them eventuating are difficult to identify with precision or confidence. The sharp adjustment that should be avoided is where creditors suffer a loss of confidence in New Zealand's debtors. This would force a substantial cut to standards of living, which a policy response designed to pro-actively reduce debt may be able to avoid. Accordingly, New Zealand's government should be vigilant in pursuing fiscal and regulatory policies that continue to build resilience through encouraging individuals to strengthen their financial position.
Keywords: E21; F32; F34; G01; 330; Saving; Current Account Deficit; Economic Imbalances; Financial Crises; Wirtschaftswachstum; Wirtschaftliche Anpassung; Neuseeland